The Dual Role of AQP4 in Cytotoxic and Vasogenic Edema Following Spinal Cord Contusion and Its Possible Association With Energy Metabolism via COX5A - Huang, Yuan; Li, Sheng-nan; Zhou, Xiu-ya; Zhang, Li-xin; Chen, Gang-xian; Wang, Ting-hua; Xia, Qing-jie; Liang, Nan; Zhang, Xiao (Frontiers in Neuroscience, 2019)
Spinal cord edema,mainly including vasogenic and cytotoxic edema,influence neurological outcome after spinal cord contusion (SCC).Aquaporin 4 (AQP4) is the most ubiquitous water channel in central nervous system (CNS),which is a rate-limiting factor in vasogenic edema expressing in brain injury,and it contributes to the formation of cytotoxic edema locating in astrocytes.However,little is known the regulatory mechanism of AQP4 within vasogenic and cytotoxic edema in SCC,and whether regulation mechanism of AQP4 is related to Cytochrome coxidase (COX5A) affecting energy metabolism.Therefore,SCC model is established by Allen’s method,and the degree of edema and neuronal area is measured.Motor function of rats is evaluated by the Basso,Beattie,and Bresnahan (BBB) scoring system.Meanwhile,AQP4 and COX5A are detected by real-time quantitative PCR (qRT-PCR) and western blot (WB).localization of targeted protein is exhibited by immunohistochemical staining (IHC) and immunofluoresce (IF).Besides,the methodology of AQP4 lentivirus-mediated RNA interference (AQP4-RNAi) is used to reveal the effect on edema of SCC and the regulating molecular mechanism. Firstly,we observe that tissue water content increase after SCC,and decrease after the peak value of tissue water content at 3 days (P<0.05) with abundant expression of AQP4 protein locating around vascular endothelial cells,which suggests that the increasing AQP4 promotes water reabsorption and improves vasogenic edema in the early stage of SCC.However,neuronal area is larger than sham group in the 7 days(P<0.05) with the total water content of spinal cord decrease.Meanwhile AQP4 migrate from vascular endothelial cells to neuronal cytomembrane,which indicates that AQP4 play a crucial role in aggravating the formation and development of cytotoxic edema in the middle stages of SCC. Secondly,AQP4-RNAi is used to elucidate the mechanism of AQP4 to edema of SCC.The neuronal area shrinks and the area of cytotoxic edema reduces after AQP4 downregulation.BBB scores is significantly higher than vector group after AQP4-RNAi at 5d,7d and 14d(P < 0.05).There is a relationship between AQP4 and COX5A shown by bioinformatics analysis.After AQP4 inhibition,expression of COX5A significantly up-regulated in the swelling astrocytes.Therefore,inhibition of AQP4 expression reduces cytotoxic edema in SCC and improves motor function,which may associate with upregulation of COX5A via affecting energy metabolism.Moreover,it isn’t clear how the inhibition of AQP4 directly causes the upregulation of COX5A.